2019
DOI: 10.1097/shk.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Pathway Inhibition Protects the Diaphragm From Sepsis-Induced Wasting and Weakness in Rat

Abstract: Sepsis is a frequent complication in patients in intensive care units (ICU). Diaphragm weakness, one of the most common symptoms observed, can lead to weaning problems during mechanical ventilation. Over the last couple of years, members of the transforming growth factor (TGF) β family, such as myostatin, activin A, and TGF-β1, have been reported to strongly trigger the activation of protein breakdown involved in muscle wasting. The aim of this study was to investigate the effect of TGF-β inhibitor LY364947 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In contrast, a progressive decrease in both muscle mass and the fiber cross-sectional area during seven days after sepsis induction has been observed in limb muscles [ 4 , 6 , 7 ]. There are several factors that can mediate sepsis-induced muscle wasting, muscle inflammation, increased autophagy, upregulation of the ubiquitin-proteasome system, and increased calpain activity and mitochondria dysfunction [ 6 , 7 , 12 , 13 ]. All these factors are induced by sepsis in both the diaphragm and limb muscles, but these responses in the diaphragm are smaller and transient in comparison with those of limb muscles, which are stronger and prolonged [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a progressive decrease in both muscle mass and the fiber cross-sectional area during seven days after sepsis induction has been observed in limb muscles [ 4 , 6 , 7 ]. There are several factors that can mediate sepsis-induced muscle wasting, muscle inflammation, increased autophagy, upregulation of the ubiquitin-proteasome system, and increased calpain activity and mitochondria dysfunction [ 6 , 7 , 12 , 13 ]. All these factors are induced by sepsis in both the diaphragm and limb muscles, but these responses in the diaphragm are smaller and transient in comparison with those of limb muscles, which are stronger and prolonged [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[49]Due to sepsis, many pathological events such as hemorrhage, edema, increase in the number of immune cells and pulmonary obstruction accompany the lungs. [50] When we examined our study, it was observed that edema, hemorrhage and in ammation focuses were moderate in sepsis groups, while edema, in ammation and hemorrhagic areas almost completely disappeared in the groups to which rasagiline was applied.…”
Section: Discussionmentioning
confidence: 79%
“…[49]Due to sepsis, many pathological events such as hemorrhage, edema, increase in the number of immune cells and pulmonary obstruction accompany the lungs. [50] When we examined our study, it was observed that edema, hemorrhage and in ammation focuses were moderate in sepsis groups, while edema, in ammation and hemorrhagic areas almost completely disappeared in the groups to which rasagiline was applied.…”
Section: Discussionmentioning
confidence: 79%